Hubungan Dukungan Sosial Orang Tua Terhadap Perkembangan Motorik Kasar Anak Usia Dini Di PAUD Gideon Wayari - Agnes Nivivita Mahakena (Institut Agama Kristen Negeri (IAKN) Ambon, 2024)
This study aims to examine the relationship between parental social support and the gross motor development of early childhood at PAUD Gideon Wayari. Early childhood is a crucial developmental period often referred to as the